Neurohormonal signaling via a sulfotransferase antagonizes insulin-like signaling to regulate a Caenorhabditis elegans stress response. Issue 1 (December 2018) - Burton, Nicholas; Dwivedi, Vivek; Burkhart, Kirk; Kaplan, Rebecca; Baugh, L.; Horvitz, H.
Abstract Insulin and insulin-like signaling regulates a broad spectrum of growth and metabolic responses to a variety of internal and environmental stimuli. For example, the inhibition of insulin-like signaling inC. elegans mediates its response to both osmotic stress and starvation. We report that in response to osmotic stress the cytosolic sulfotransferase SSU-1 antagonizes insulin-like signaling and promotes developmental arrest. Both SSU-1 and the DAF-16 FOXO transcription factor, which is activated when insulin signaling is low, are needed to drive specific responses to reduced insulin-like signaling. We demonstrate that SSU-1 functions in a single pair of sensory neurons to control intercellular signaling via the nuclear hormone receptor NHR-1 and promote both the specific transcriptional response to osmotic stress and altered lysophosphatidylcholine metabolism. Our results show the requirement of a sulfotransferase–nuclear hormone receptor neurohormonal signaling pathway for some but not all consequences of reduced insulin-like signaling. Reduced insulin-like signaling is required forC. elegans response to many environmental stressors, but how distinct outcomes are achieved is unknown. The authors show that the cytosolic sulfotransferase SSU-1 controls neurohormonal signaling via NHR-1 to specify the animals' osmotic stress response.